Promotional Strategies to Increase Sales on TikTok Shop in the Digital Era from an Islamic Perspective (Study on the Beautystore.Mms TikTok Account in Baturaja) - Welin Ariska Nenti; Rofiqoh , Rofiqoh; Reny Shinta Sari (LP2M IAIN Palopo, 2025)
The development of information technology and digital marketing, particularly through the social media platform TikTok, has changed the product promotion paradigm among small and medium enterprises (MSMEs). This study examines the digital promotion strategy of the Beautystore.Mms TikTok account in Baturaja and its alignment with Islamic economic principles. Using a qualitative, case study-based approach, data was collected through interviews, observation, and documentation. The results show that the use of TikTok's creative features, such as TikTok ads, customer testimonials, and incentives in the form of gifts and free shipping, successfully increased sales and customer loyalty. This promotional strategy is comprehensively integrated into the marketing mix (4Ps): certified halal products, competitive pricing, timely distribution, and innovative promotions. Most business practices have adopted Islamic ethical and sharia standards, particularly the principles of honesty, justice, and trustworthiness, although the monotheistic aspects of Islamic economics have not been fully internalized. This study confirms that harmonizing modern digital marketing technology and Islamic business ethics can create an economically, morally, and socially sustainable MSME business model in the digital era.